Morphological variation of mandibular molars in Rohilkhand population: An original research - Tanu Singh; Saurav Bathla; Saurav Kumar Dutta; Minhaj Ahmed Amer Mohammed; Navdeep Jethi; Harsh Chansoria; Saraswathi Sravani Pulluri (Wolters Kluwer Medknow Publications, 2024)
Introduction: In-depth knowledge of common and aberrant pulp morphology is essential for appropriate diagnosis and treatment planning before commencing root canal treatment. The radicular morphology of mandibular molars has been extensively studied. Considerable variation in the number of canals and roots found in these teeth has been reported. Aim: The purpose of this study is to investigate the root canal morphology of the mandibular molars among the Rohilkhand population using Dentascan. Materials and Methods: Dentascan images of mandibular molar were taken from 99 extracted teeth that were collected from the Department of Oral Surgery and Maxillofacial Surgery, Institute of Dental Sciences, Bareilly, and private clinics. The examination of root canal systems of the teeth was based on Vertucci's classification. Results: The mandibular molar (n = 99) were taken. Out of the 99 teeth examined, three canals were seen in 60 (60.6%) teeth, four canals in 39 (39.4%) teeth, 3% had extra distal roots, and 6% with C-shaped canals. Conclusion: Among mandibular first molars, only 3% had three roots. Mesial roots of the first molar typically present with two canals and two apical foramina with type IV or II canal configuration. Most distal roots of the first molar presented with a type I canal configuration. The remainder were distributed mainly between types II, IV, III, and V. Among 99 mandibular molars, 6% had single C-shaped roots.